You wouldn't want to live without insects! - Rooney, Anne.; Antram, David, 1958-; Salariya, David (New York : Franklin Watts, an imprint of Scholastic Inc., 2015)
Uses humor in both text and illustrations to describe the beneficial roles insects play.
"Created and designed by David Salariya"--T.p.
School Library Journal, November 2014
Includes index.
4.7
3-6
Keywords: Insects -- Juvenile literature; Insects; Insects